Traditional uses, phytochemistry, and pharmacology of Ficus hispida L.f.: A review. (10th February 2020) - Cheng, Jia-xin; Zhang, Bo-dou; Zhu, Wan-fang; Zhang, Chao-feng; Qin, Yi-min; Abe, Masahiko; Akihisa, Toshihiro; Liu, Wen-yuan; Feng, Feng; Zhang, Jie
Abstract: Ethnopharmacological relevance: Ficus hispida L.f. (Moraceae) has long been used as a traditional medicine in India, China, Sri Lanka, Australia, and Myanmar in the treatment of diarrhea, ulcer, anemia, diabetes, inflammation, and cancer. Aim of the review: This review provides a systematic comment on the botany, traditional uses, and phytochemical and pharmacological studies of F. hispida, with an aim to make critical update of the current knowledge and obtain opportunities for further therapeutic potential. Materials and methods: The information was derived from scientific literature databases including PubMed, Baidu Scholar, Google Scholar, Web of Science, and Science Direct. Additional information was gathered from books, Ph.D. and M.Sc. dissertations, and unpublished materials. Results and discussion: F. hispida is used especially in Chinese and Indian traditional medical systems as a remedy for skin disorders, respiratory diseases, and urinary diseases. Wound healing, anti-inflammatory, antinociceptive, sedative, antidiarrheal, antiulcer, antimicrobial, antioxidant, hepatoprotective, antineoplastic, and antidiabetic activities have been reported for crude extracts and isolated metabolites, but the methodologies in these studies often have inadequate design and low technical quality. More than 76 compounds have been isolated from F. hispida, including sesquiterpenoids and triterpenoids, flavonoids, coumarins, phenylpropionic acids, benzoic acid derivatives, alkaloids, steroids, other glycosides, and alkanes, but the method of bioassay-guided fractionation is seldom applied in the isolation from F. hispida . Conclusion: F. hispida is used widely in traditional medicines and has multiple pharmacological effects that could support traditional uses. However, pharmacological studies should be viewed with caution because of the inappropriate experimental design. More in vitro and in vivo research is urgently needed to study the molecular mechanisms and assess the effective and safe dose of F. hispida . Graphical abstract: Image 1